Association between playing cards/mahjong and risk of incident dementia among the Chinese older adults: a prospective cohort study - Tian, Gang; Shuai, Jingliang; Li, Rui; Zhou, Tong; Shi, Yan; Cheng, Gang; Yan, Yan (Frontiers in Aging Neuroscience, 2022)
Objectives: Studies have shown that the frequent participation of the elderly in cognitive stimulation activities is associated with a reduced risk of dementia, but the prospective evidence of this association is limited. Methods: We used data from a prospective cohort study of the Chinese Longitudinal Healthy Longevity Survey (CLHLS), and included 11,821 community-living Chinese individuals aged 65 years or older at 2008 baseline who were free of dementia, and were followed up every 2–3 years until 2018. Cox proportional hazards models were applied to generate the hazard ratios (HRs) and 95% confidence intervals (CIs) for analyzing the associations between the frequency of playing cards/mahjong and the incidence of dementia. Results: A total of 821 participants were diagnosed with dementia during the 10-year follow-up. The average age of patients with dementia and non dementia were 89 and 90 years old, respectively. Compared with participants who rarely or never played cards/mahjong, participants who played cards/mahjong almost every day had a significantly lower risk of dementia (HR = 0.63; 95%CI, 0.42–0.95) after the multivariable-adjusted model. Similar results were observed in subgroup analyses based on sex (male: HR = 0.52, 0.28–0.96; female: HR = 0.62, 0.36–0.98), age (<85years: HR = 0.55, 0.32–0.89), regularly exercise (yes: HR = 0.44, 0.28–0.87) and MMSE score [above median (25): HR = 0.66, 0.41–0.92]. Conclusions: Playing cards/mahjong in the elderly may contribute to reducing the risk of dementia.